Literature review and analysis of wrist rehabilitation devices - Oliveira, Ana (2018)
The wrist is a very important joint of the human body, involved in several basic activities. When the wrist is injured, it causes a significant disturbance in the quality of life. Therefore, patients have difficulty to perform some tasks. The main devices used in rehabilitation clinics and hospitals are very simple and often directed to only one type of movement, not providing the complete rehabilitation of the wrist. In order to solve this problem, new devices, therapies and systems for wrist rehabilitation have been developed. These mainly consist of virtual reality therapies, exoskeletons, gloves and vibratory therapies. The performed analysis showed that an ideal wrist rehabilitation device does not exist, but many devices complement each other and provide a good therapy. Recently it has been indicated vibratory therapies to aid the rehabilitation of traumatic injuries. These have shown very positive effects, even in the wrist rehabilitation. In future developments, this characteristic should be implemented, through the development of a portable vibratory device with frequencies and magnitudes of vibration appropriate to the human body.